Development of a hybrid PV/wind based power converter - Zaw, Htet Aung (2013)
Because of the global warming and limited natural resources and fuels, development of renewable energy such as wind energy, solar energy and bio-fuel energy are more popular in nowadays. At the same time, power electronic technology is also become popular in as the voltage and current from renewable energy are unstable and uncontrollable. The objective of this final year project (FYP) is to research the various methods of AC-DC and DC-AC conversions, to test and simulate the results with the use of PSIM software. The report is categorized into five main sections: Introduction, Literature Review, Design and Calculations,System Simulation and Results, Conclusion and Recommendations. The overall project description is described under Introduction section to give the readers about the overall project impression. Next, the theories and the calculations needed for the project are described under Literature Review section. Design and Calculations section will describe various calculations used in designing individual components.System Simulationsand Results section will describe the simulation and output of the project with the help of PSIM software followed by Conclusion and Recommendations section for the conclusion of the project and future expansion and recommendations.